Former Yugoslav Republic of Macedonia Employment and Job Creation : Labor Market Assessment 2007-2011 - World Bank (Washington, DC, 2015)
This note forms part of a broader engagement between the World Bank and the Government of FYR Macedonia on how to foster more and better jobs and make sure that more marginalized groups, women, low earners, skilled and unskilled youth, for example - can participate and benefit from those jobs. It focuses on providing updated labor market diagnostics based on the labor force surveys between 2007 and 2011. The findings will be used as a basis for further policy analysis. The remainder of this note is organized as follows. Section two describes labor market developments since 2007 and the conditions prevailing in 2011. Subsequent sections address the remaining challenges and key policy options. The third section thus focuses on raising productivity – critical to national economic development and to ensure sustainable increases in earnings over time in Macedonia. The fourth section discusses the generational divide in terms of challenges in labor market opportunities for the younger versus older generations. The fifth section looks at workers that are particularly disadvantaged in the labor market with a particular focus on women. The sixth section concludes with the policy levers that may help Macedonia move forward on the jobs agenda.